The Influence of Interactivity, Hedonic Motivation, and Performance Expectations on Purchase Intentions of HMNS Perfumery on the Shopee e-commerce platform - Nugraheni Pramestiti; Drs. Anas Hidayat M.B.A., Ph.D (International Journal of Economics, Business and Innovation Research, 2024)
Most social media users like fast and easy e-commerce transactions. Effective communication between buyers and sellers influences buyer satisfaction when shopping online. Active public participation in online shopping drives the growth of e-commerce in Indonesia. This study discusses important elements that influence purchase intention in using e-commerce, such as interactivity, hedonic motivation, and performance expectancy. This study looks at the cause-and-effect relationships between the variables considered through hypothesis testing. This research data was used by testing primary data obtained from respondents using quantitative calculation research methods. This research aims to examine the component that drive the intention to buy goods online via e-commerce and analyze the function of each variable. There are 251 research samples from Shopee e-commerce users who were familiar with the HMNS Perfumery brand through an online survey (google form) and analyzed using SPSS and PLS-SEM by SmartPLS. The research results reveal that interactivity, hedonic motivation, and performance expectancy have a positive and significant effect on online purchase intentions through e-commerce. This study adds to the marketing literature on online purchase intentions through e-commerce. In addition, this study suggests marketing managers to manage important factors that can influence potential consumers' online purchasing decisions so that they can increase their sales.